Investigating How Families Experience School Criminalization - Tate, Monique (2016)
Public school students across the United States have been criminalized for minor youth behavior issues such as truancy, defiance, and minor fighting incidents. The presence of law enforcement is expanding in school spaces, increasing the likelihood of young students facing court systems for minor offenses. Criminalization of students is counterproductive considering schools are designed to promote student growth and development. Little is known about how students and parents experience school criminalization. The purpose of this multi-case study, based on Freire's conceptual framework of critical consciousness, was to investigate how a small group of families experienced school criminalization. Three families of youths who had been criminalized for minor school offences were recruited using community partners as referral sources. Interviews were conducted with parents using a semi-structured protocol, and data were also obtained from school and court records provided by parents. Data were triangulated, summarized as case descriptions, member checked, and then cross-theme analyzed based on Gibbs and Taylor's approach for emergent themes. Study results demonstrated that these families felt trapped between two institutions and experienced fear and frustration trying to deal with both systems. Participants also recommended ways parents and schools might improve discipline for minor offences. This study will influence social change by informing school and juvenile justice discipline policy reform about working with two systems in managing student behavior concerns. In addition, the interview protocol can be used by human services professionals to help improve understanding of clients faced with school criminalization issues